Vernacular Architecture and Urban Design : A Strategy for Place-Making in St. John’s, Newfoundland - Mellin, Robert (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1995)
For some years now, urban planners have begun to rely more on quantitative and qualitative data gamered from vernacular architecture as they seek to develop new strategies for meeting the changing housing needs of city-dwellers. In this article, the author examines older residential areas in St. John’s, Newfoundland, with a view to finding useful ideas for consolidating and improving the existing housing stock in terms of the strengths of traditional neighbourhoods. History, landscape, social values and économie factors ail corne into view in Mellin’s proposed approach to enlightened residential redevelopment.